MANAGING ULCERATIVE COLITIS BY INCREASING HYDROGEN PRODUCTION VIA ORAL ADMINISTRATION OF ACARBOSE - Zhu, Jian-Hong; Zhang, De-qing; Chen, Wei-chang (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to investigate ulcerative colitis management through oral administration of acarbose. Acarbose has gained importance as a drug used widely to treat Diabetes Mellitus Type 2,as it acts on the small intestine by competitively inhibiting enzymes that delay the release of glucose from complex carbohydrates, thereby specifically reducing postprandial glucose excursion. The main side-effect of treatment with Acarbose, flatulence, occurs when undigested carbohydrates are fermented by colonic bacteria, resulting in considerable amounts of hydrogen. We found that the enteric benefits of Acarbose are partly due to be their ability to neutralise oxidative stress via increased production of H2 in the gastrointestinal tract. Therefore, some symptoms of ulcerative colitis in human beings can be ameliorated by Acarbose.